Peran Pesantren Modern Dalam Mempersiapkan Generasi Z Sebagai Pembelajar Masa Depan Berlandaskan Nilai-Nilai Islam - Amri, Muhammad Farizal (Atthiflah: Journal of Early Childhood Islamic Education, 2025)
Islamic boarding schools, or “pesantren”, are among Indonesia's oldest and most unique educational institutions. Rooted in rich cultural and religious traditions, pesantren have historically served as centers of Islamic learning and moral fortresses for society. As a dynamic and adaptive institution, pesantren continue to play a pivotal role in addressing societal challenges and advancing education. Today, pesantren face a new challenge in preparing Generation Z (Gen Z), a tech-savvy, ambitious, and rapidly evolving demographic.This study examines the role of pesantren in equipping Gen Z as future learners imbued with Islamic values. It highlights the potential of modern pesantren to integrate religious teachings with contemporary technological advancements. Utilizing a qualitative approach and literature review method, the study analyzes how pesantren adapt to the evolving characteristics of Gen Z. By embedding moral values such as independence, discipline, honesty, and collaboration, pesantren provide a comprehensive educational model that balances intellectual and spiritual development. The findings underscore the importance of modern pesantren in bridging traditional Islamic education with the demands of the digital age. Case studies of institutions like Pondok Modern Darussalam Gontor and Pesantren Teknologi Majapahit demonstrate how pesantren adopt modern methodologies while preserving their Islamic identity. By fostering a holistic learning environment, modern pesantren empower Gen Z to navigate technological advancements without compromising their moral and religious values. Thus, pesantren emerge as pivotal institutions in preparing future generations to meet global challenges while maintaining their Islamic identity.